Study of the chemical content and antimicrobial activity of Iraqi butter milk of cows and buffaloes - Raghad Saad Al Musa; Najla Hussen. Al Garory (Zien Journals, 2022)
This study was conducted to estimate the chemical content of cow and buffalo milk fermented with four types of commercial starters, namely YO-MIX 495, YO-MIX S31, YO-MIX 505, and YO-MIX 511, after activation of the prefix bacteria for the manufacture of yogurt and stir it by electrophoresis and determination of the chemical content using a device. Anlyzer Eko milk, pH, acidity percentage, and carbohydrates percentage by HPLC technique and evaluation of the inhibitory activity of mixed milk against five types of pathogenic bacteria, namely Bacillus cereus, Staphylococcus aureus, E.Coli, Enterobacter aerogenes and Pseudomonas aeruginosa The results showed that the fermentation process had an effect on the chemical content, pH, and surface acidity, as the highest value of pH, acidity, protein, fat, ash, solids, and moisture for cow’s milk treatments reached 4.53, 0.84, 2.57, 1.20, 0.61, 6.66 and 93.93%, respectively. For buffalo milk treatments, 4.41, 0.85, 2.76, 1.30, 0.72, 7.08, and 93.51%, respectively, the highest value of carbohydrates is for lactose in cow's milk butter milk, 0.80 - 1.96%, and in buffalo's milk buttermilk 2.44-3.30%, the results also showed that the milk has an inhibitory activity against Gram-positive. Negative bacteria were higher in milk made from buffalo than in cow buttermilk. The highest inhibitory diameter was 12 mm for gram-positive bacteria and 9 mm for gram-negative bacteria.
Keywords: shaken milk; antibacterial activity; MacFarland; pathogenic bacteria